Frequency Tracking Control Strategy for Resonant Inverter Based on Pulse Density Modulation - ZHU Hui; PENG Yonglong; LU Zhibin; LI Yabin (Kongzhi Yu Xinxi Jishu)
It presents an improved frequency tracking control strategy aiming to the problems of conventional pulse density modulation for induction heating power supply in output power with level and operating frequency re-locking as recovering from natural attenuation to the output power state. Output load current is applied to fast frequency tracking, thus the phase-locked loop (PLL) has enough time to lock the phase, and when the load current is dropping to a very small value, that is, entering into a natural attenuation state, the sample and hold (S/H) circuit in modified phase-locked loop (MPLL) ensures power inverter operating in the vicinity of resonant frequency. The corresponding simulation experiments are carried out through Matlab/Simulink, and pulse-symmetrical modulation is chosen for power modulation, which can decrease attenuation of output current and ensure the inverter circuit working at zero current switching (ZCS) state and zero voltage switching (ZVS) state.